Integrationsarbeit mit eingewanderten Jugendlichen mit VaKE (Values and Knowledge Education) - Patry, Jean-Luc; Weyringer, Sieglinde; Aichinger, Kathrin; Weinberger, Alfred (International Dialogues on Education Journal, 2016)
For a successful integration of young immigrants in the new culture and its values it is not sufficient that they acquire knowledge about the society; rather, moral and values education with respect to the justification of the respective values is required. We present an educational concept that permits to combine knowledge acquisition and moral education: “Values and Knowledge Education” (VaKE). The theoretical base and the practical steps are presented. Then a pilot study with a group of minor migrants about the topic of democracy and the most important results are described. The discussion addresses the question of applicability.